Major depression and mother-infant interaction : Affect-related behaviors in presence of a major depressive episode and after remission compared to non-depressed control mothers - Stefenelli, Ulrich; Justus Liebig University Giessen (My University, 2011)
A detrimental effect of maternal depression on the way mother and infant interact is consistently reported, yet there is a shortage of rigorous laboratory studies focusing on major depression and the effects after remission. In the literature detrimental effects of parental depression on offspring are summarized under the notion depression runs in families . Although there is a consensus that depression is partly hereditary, a main focus on genetic pathways and a neglect of parental behaviors have been criticized for the inconsistency of heritability estimates and the non-specificity of adverse child-effects such as heightened externalization behaviors being consistently reported in children of depressed parents. A body of literature has suggested that dysfunctional interactive patterns of mother and infant may have mediator functions in how maternal depression affects infants in terms of adverse child outcomes. The present research pursued two basic models focussing on disturbances of affect exchanges. Gergely and Watson s model (maternal affect mirroring as social biofeedback) proposes that maternal affect can be used as an infant-regulation mechanism. Accordingly, flat affect of a depressed mother is suggested to have disruptive quality on these processes and decreased affect-mirroring may increase the risk of a failed regulation or controllability of infant affects. Impaired-parenting models predict that a maternal major depression will restrict resources and therefore change the reinforcement conditions for the infant. On the other hand transient child-disturbance approaches suggest that adverse infant effects and dysfunctional interactions will disappear after the remission of maternal major depression. Based on predictions such as those above, a prospective, highly standardized, observer-blind, controlled laboratory trial with repeated measurement was conducted: 59 mothers in total, 24 with a clinical diagnosis of major depression, together with their infants and 35 control dyads were videotaped during face-to-face play interactions in the laboratory. Diagnoses strictly followed the DSM IV criteria for major depression. The mothers were instructed to interact with the infant as they would normally do at home and were assessed when the mother was still in an episode of a major depression and re-assessed after the remission of the depression (17 of 24; 71%), at a median of 2 months. Control mothers were re-assessed after a comparable period of time (25 of 35; 71%). Affect-related behaviors were coded during a still-face procedure (two free interaction phases interrupted by a phase of maternal still-face, i.e., a period of minimized maternal affect expressions). Sample size attrition had no effect on primary or secondary parameters. The results of the confirmative 1st-type-error-adjusted comparisons showed no depression-related impairment of any type. There were no impairments to express or mirror affects both in mothers and infants. Depressed mothers did not behave in an under-stimulating manner. Infants of a depressed mother were not differently affected by the short still-face period. They were neither hypo-active nor hyper-active. The maternal ability to maintain interactions and to respond was not decreased. Contingent responses in infants were not impaired. After a depression remission, there were no changes in difficult infant behavior such as protest and withdrawal. Infants did not show signs of rejection, or unwillingness to interact, nor were there spirals of negativity. Even high engagement of depressed mothers was not associated with heightened infant negativity, as predicted by interpersonal stress approaches. Infants of depressed mothers did not show less adjustability or controllability, as suggested by regulation approaches. Thus, there was no sign that a clinical diagnosis of major depression has any predictive value with respect to observable affect-related behaviors, either in mothers or infants. Beyond that, a multivariate nonparametric test for equivalence (Wei-Lachin test) showed that dyads with a depressed mother were significantly equivalent compared to controls. The lack of predictability of a maternal major depression diagnosis is surprising, given the large range of publications concluding the well-predictive properties of (mostly self-rated) depression. This low predictive value is discussed with respect to Rutter s (1990) notion that depression may not have causal but indicative function and the resilience in infants may be considerable. The results open up for the possibility that maternal major depression may not generalize on behavior towards an infant and may therefore not be reflected in infant behavior.
Mütter mit majorer Depression und Mutter-Kind Interaktion : Affekt-bezogene Verhaltensweisen während einer depressiven Episode und nach Remission der Majoren Depression im Vergleich zu einer nicht-depressiven Kontrollgruppe
Keywords: Majore Depression; Mutter-Kind Interaktion; Affekte und Verhalten; depressive Episode; Remission der Depression; major depression; remission; mother-infant interaction; ddc:150